The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2207/qjjws.27.4s
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Metal Vapor Behavior with Multi-diffusion System in TIG Welding of Stainless Steel

Abstract: In the present paper, a TIG arc in helium or argon is modeled taking into account the contamination of the plasma by the metal vapor from a stainless-steel weld pool. Iron, chromium and manganese are considered as the metal vapor species in this model. A viscosity approximation is used to express the diffusion coefficient in terms of the viscosities of the shielding gas and the metal vapor. The time-dependent two-dimensional distributions of temperature, velocity and metal vapor concentrations of iron, chromiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Iron vapour is swept upward without being dispersed due to the flow rate being increased by the constricted nozzle. It is thought that the decrease in arc plasma temperature caused by the presence of iron vapour is controlled due to this [6,10]. Figure 5 shows the thermal flux distribution at the base metal surface.…”
Section: Governing Equationmentioning
confidence: 99%
“…Iron vapour is swept upward without being dispersed due to the flow rate being increased by the constricted nozzle. It is thought that the decrease in arc plasma temperature caused by the presence of iron vapour is controlled due to this [6,10]. Figure 5 shows the thermal flux distribution at the base metal surface.…”
Section: Governing Equationmentioning
confidence: 99%
“…The simulation model employed in this study consists of a GTA welding model [8] and a fume formation model. Additionally, a GMA welding model taking account of metal transfer process has also been developed for coupling that with the fume formation model.…”
Section: Simulation Modelmentioning
confidence: 99%
“…n 1 is the number density of iron atoms. is a dimensionless surface energy expressed by equation (8).…”
Section: Homogeneous Nucleation Model Of Primary Particlementioning
confidence: 99%
See 1 more Smart Citation
“…The measurements and modelling of Gonzalez et al [10] showed that the presence of iron vapour resulted in a reduction of the temperature of an argon arc by about 1000 K within 2 mm of the anode in a 20 mm-long arc with 90 A arc current. Computational modelling of the metal vapours produced from stainless steel workpieces for argon and helium arcs likewise predicted that the vapour would remain confined to the region close to the anode workpiece [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%